The study of the catholic tradition of the Kirk: Scoto-Catholics and the worship of the reformers - Young, Douglas MacMurray (Studies in church history, 1997)
James Cooper, Professor of Ecclesiastical History at Glasgow University and a prominent High Churchman, once remarked that one of the main reasons for the Catholic revival in the Church of Scotland in the late nineteenth century was the renewed study of the history of the Scottish Church. The Catholic revival, or Scoto-Catholic movement, found expression in the formation of the Scottish Church Society in 1892. The High Churchmen who formed the Society considered that a Catholic position was no novelty in the Kirk. According to Henry J. Wotherspoon, one of the leading theologians of the movement, the Presbyterian was from the first ‘the High Catholic of Puritanism’, and it followed that the material for a catholic revival lay at hand in the traditions of the Church. In its classic form and confessional position, he said, Presbyterianism discerned the Kingship of Christ; it asserted the Church as a Divine imperium, ‘visible, universal, and divinely ordered’, independent and autonomous; it maintained Episcopate, none the less that it was Episcopate put into commission; it asserted for the Presbyterate Apostolic Succession; it held a very distinct sacramental system, cumbered only by the endeavour to combine it with a doctrine of election; it exercised a vigorous discipline; it adhered to the oecumenical creeds in every term of their definitions and on that ground claimed to be acknowledged as Catholic.